2010
DOI: 10.1039/c004223d
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity enhancement in functionalization of C–H bonds: A review

Abstract: The selectivity is an extremely important characteristic of a chemical reaction. This review deals mainly with supramolecular and nano-chemical approaches to the problem of selectivity enhancement in various functionalizations of C-H compounds. Enzyme mimics is a very fruitful method to achieve the predominant formation of desirable products and isomers. By obstructing the approach of certain C-H bonds of a substrate to the active catalytic centre we simultaneously increase the relative reactivity of other fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(66 citation statements)
references
References 158 publications
6
60
0
Order By: Relevance
“…We proposed and developed a simple method for analysis of alkyl hydroperoxides generated in various alkane oxidations in solutions [11][12][13][247][248][249][250][251][252]). A chemist can find that, if the direct injection of a reaction sample into the chromatograph gave comparable amounts of cyclohexanol and cyclohexanone ( Figure 16, Figure 17a), the reduction of the sample with PPh 3 prior to GC analysis led to the noticeable predominance of the alcohol (Figure 17b).…”
Section: Detection and Determination Of Alkyl Hydroperoxides Comparinmentioning
confidence: 99%
See 1 more Smart Citation
“…We proposed and developed a simple method for analysis of alkyl hydroperoxides generated in various alkane oxidations in solutions [11][12][13][247][248][249][250][251][252]). A chemist can find that, if the direct injection of a reaction sample into the chromatograph gave comparable amounts of cyclohexanol and cyclohexanone ( Figure 16, Figure 17a), the reduction of the sample with PPh 3 prior to GC analysis led to the noticeable predominance of the alcohol (Figure 17b).…”
Section: Detection and Determination Of Alkyl Hydroperoxides Comparinmentioning
confidence: 99%
“…This review is devoted to functionalization of carbon-hydrogen bonds [1][2][3][4][5][6][7][8][9][10][11][12][13] in various organic compounds, which is a very important process both from academic and practical point of view. Replacing hydrogen atoms in carbon-hydrogen compounds by functional groups X leads to valuable functionalized C-X compounds (Scheme 1a).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, cyclohexane gives minimum number of oxidation products which are easily identified by the GC method. As demonstrated previously in other oxidations [19,[59][60][61][62][63][64][65][66][67][68], if the direct injection of a reaction sample into the chromatograph gave comparable amounts of cyclohexanol and cyclohexanone, the reduction of the sample with PPh3 (or certain sulfides) prior to GC analysis in many cases led to the noticeable predominance of the alcohol (Figure 8). The comparison of the results obtained before and after the reduction clearly indicated that cyclohexyl hydroperoxide was formed as the main primary product.…”
Section: Catalytic Oxidation Of Alcohols and Hydrocarbonsmentioning
confidence: 79%
“…C(1) : C(2) : C(3) : C(4) = 1.0 : 6.7 : 6.6 : 6.1. It can be seen that hydrogen atoms in position 4 posess lower activity, aparently due to some sterical hindrance [50,57,60]. The bond-selectivity parameter (1° : 2° : 3°; the relative normalized reactivities of hydrogen atoms at the primary, secondary and tertiary carbons) in the oxidation of methylcyclohexane (1.0 : 6.7 : 17.5) is close to the corresponding values found for the systems oxidizing alkanes with hydroxyl radicals (see, for example, Refs.…”
Section: Selectivity In the Alkane Oxidationsmentioning
confidence: 99%
See 1 more Smart Citation